Commissioning and testing of pre-series triple GEM prototypes for CBM-MuCh in the mCBM experiment at the SIS18 facility of GSI. (3rd September 2021) - Kumar, A.; Agarwal, A.; Chatterjee, S.; Chattopadhyay, S.; Dubey, A.K.; Ghosh, C.; Nandy, E.; Negi, V.; Prasad, S.K.; Saini, J.; Singhal, V.; Singh, O.; et al.
Abstract: Large area triple GEM chambers will be employed in the first two stations of the MuCh system of the CBM experiment at the upcoming Facility for Antiproton and Ion Research FAIR in Darmstadt/Germany. The GEM detectors have been designed to take data at an unprecedented interaction rate (up to 10 MHz) in nucleus-nucleus collisions in CBM at FAIR. Real-size trapezoidal modules have been installed in the mCBM experiment and tested in nucleus-nucleus collisions at the SIS18 beamline of GSI as a part of the FAIR Phase-0 program. In this report, we discuss the design, installation, commissioning, and response of these GEM modules in detail. The response has been studied using the self-triggered readout electronics. In free-streaming data, the first attempt on an event building based on the timestamps of hits has been carried out, resulting in the observation of clear spatial correlations between the GEM modules in the mCBM setup for the first time. Accordingly, a time resolution of ∼15 ns have been obtained for the GEM detectors. Gain uniformity & cluster characteristics have also been studied.